The workforce for rehabilitation in primary health care in Brazil - Debora Bernardo da Silva; Taciana Rocha dos Santos Sixel; Arthur de Almeida Medeiros; Paulo Henrique dos Santos Mota; Aylene Bousquat; Ana Carolina Basso Schmitt (BMC, 2021)
Abstract Background Studies on the workforce in rehabilitation in primary health care services are still unusual in health systems analysis. Data on the health worker density at the subnational level in rehabilitation in primary health care are not commonly observed in most health systems. Nevertheless, these data are core for the system's planning and essential for finding the balance between the composition, distribution, and number of workers for rehabilitation actions. Objective This study aims to analyze the temporal space distribution of health professionals with higher education who performed rehabilitation actions in primary health care in Brazil from 2007 to 2020. Method This is an ecological, time-series study on the supply of physiotherapists, audiologists, psychologists, and occupational therapists in primary health care, vis-a-vis the implementation of the Brazilian health policy denominated the Integrated Health Service Network for People with Disabilities. The data were obtained from the National Registry of Health Facilities. The period of analysis was from 2007 to 2020. The health worker density coefficient was calculated per 10,000 inhabitants annually, considering the five geographic regions of Brazil. The time trends of the coefficient of health professionals per year in Brazil and geographic regions were analyzed. For this purpose, joinpoint regression analysis was carried out. The average annual percentage variation was estimated, considering the respective confidence interval of 95%. Results In 2007, there were 0.12 physiotherapists/10,000 inhabitants (2326), 0.05 audiologists/10,000 inhabitants (1024), and 0.205 psychologists/10,000 inhabitants (3762). In 2020, there was an increase in the coefficient of professionals/10,000 inhabitants in all professional categories to 0.47 psychologists (> 268.1%), 0.46 physiotherapists (> 424.8%), 0.14 audiologists (> 297.1%), and 0.04 occupational therapists (> 504.5%). There was a significant increase in the supply of physiotherapists (AAPC: 10.8), audiologists (AAPC: 7.6), psychologists (AAPC: 6.8), and occupational therapists (AAPC: 28.3), with little regional variation. Conclusion Public health policies for rehabilitation have contributed to an increase in the workforce caring for people with disabilities in primary health care services. An increase in the workforce of physiotherapists, audiologists, psychologists, and occupational therapists was observed throughout the period studied in all regions.